Efek Moderasi Risiko Sistematis Pada Pengaruh Profitabilitas, Risiko Leverage, dan Pertumbuhan Aktiva Terhadap Nilai Perusahaan Sektor Industri Manufaktur Yang Listing di Bursa Efek Indonesia - Herawati, Herawati; Iskandar, Deni; Lumbantobing, Rudolf (Manajemen Bisnis Kompetensi, 2018)
This research aims to investigate the interaction effects between profitability, asset growth and degree of total leverage with systematic risk which might strengthen or weaken the effect of those variables on firm value. Data in this study was analyzed by using moderated regression analysis (MRA) to analyze the moderating variable effect of the independent variables on firm value. The results revealed that (1) profitability significant positively effects on firm value. But asset growth and degree of total leverage have not significantly affect the firm value. (2) Systematic risk as a moderator variable has significant positively mediate the influence of profitability toward firm value. The positive effect of profitability toward firm value should increase (decrease) while the lower (greater) systematic risk. (3) Systematic risk has not significantly moderate the influence of asset growth and degree of total leverage toward firm value. Keywords: return on asset, asset growth, total leverage, systematic risk, firm value